2010
DOI: 10.1353/foc.2010.0002
|View full text |Cite
|
Sign up to set email alerts
|

Fragile Families and Child Wellbeing

Abstract: Summary Jane Waldfogel, Terry-Ann Craigie, and Jeanne Brooks-Gunn review recent studies that use data from the Fragile Families and Child Wellbeing Study (FFCWS) to examine why children who grow up in single-mother and cohabiting families fare worse than children born into married-couple households. They also present findings from their own new research. Analysts have investigated five key pathways through which family structure might influence child well-being: parental resources, parental mental health, pare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
283
3
12

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 368 publications
(312 citation statements)
references
References 42 publications
14
283
3
12
Order By: Relevance
“…All of these exposures were frequently cited by our participants and have been shown in other studies to contribute to poor health outcomes. [75][76][77][78][79][80][81][82][83] Experiences such as harsh parenting, which negatively affect child well-being but may not be perceived as stressors, also should be considered. However, before including any of these measures in any formal ACE assessment, more research must be done to examine the relative contribution of these additional experiences to health outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…All of these exposures were frequently cited by our participants and have been shown in other studies to contribute to poor health outcomes. [75][76][77][78][79][80][81][82][83] Experiences such as harsh parenting, which negatively affect child well-being but may not be perceived as stressors, also should be considered. However, before including any of these measures in any formal ACE assessment, more research must be done to examine the relative contribution of these additional experiences to health outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Farajzadegan et al (Farajzadegan, Koosha, Sufi, & Keshvari, 2013) examined the relationship between family functioning and well-being of women and concluded that dysfunctional family function affects women's quality of life and well-being. Waldfogel et al (Waldfogel, Craigie, & Brooks-Gunn, 2010) in a study on fragile families (single unmarried parent) and the child's sense of well-being, examined aggressive behavior, anxiety, and depression in children of these families. They concluded that the level of aggressive behavior, depression, and anxiety, which are indicators of well-being, was higher in children of fragile and vulnerable families compared to normal families and have a negative impact on family functioning.…”
Section: Discussionmentioning
confidence: 99%
“…It is more likely subsequent to a parental divorce (condition 1) and is associated with high levels of parenting stress and lower-quality parent-child relationships leading to lower attainment among children (condition 2) (Beck et al 2010;Cavanagh, Crissey, and Raley 2008;Cavanagh and Huston 2006;Halpern-Meekin and Turney 2016;Lee and McLanahan 2015;Osborne and McLanahan 2007;Thomson and McLanahan 2012;Waldfogel, Craigie, and Brooks-Gunn 2010;Wu and Martinson 1993;Wu and Thomson 2001). Instability is likely to vary across families.…”
Section: Mediating Effects Of Parental Divorce On Children's Outcomesmentioning
confidence: 99%
“…Nevertheless, the negative consequences for children experiencing family disruption endured (Amato 2001;McLanahan, Tach, and Schneider 2013). A substantial literature links parental divorce to lower levels of children's educational attainment, particularly high school completion (e.g., Amato 2001;Fomby and Cherlin 2007;Lang and Zargorsky 2001;Lee and McLanahan 2015;McLanahan and Percheski 2008;McLanahan, Tach, and Schneider 2013;Seltzer 1994;Sigle-Rushton and McLanahan 2004;Waldfogel, Craigie, and Brooks-Gunn 2010;Wu and Martinson 1993). 1 Scholars studying the causal effects of parental divorce on children have primarily relied on observational data, as divorce is a social phenomenon not subject to experimental manipulation.…”
Section: Introductionmentioning
confidence: 99%